LIDAR OBSERVATION ABOVE SVALBARD, NORWAY IN THE WINTER OF 1996/97 : Characteristics of Backscattering Ratio and Depolarization Ratio of PSC Particles - シライシ, コウイチ; フジワラ, モトオ; アユカワ, シゲル; イワサカ, ヤスノブ; シバタ, タカシ; アダチ, ヒロシ; サカイ, テツ; タムラ, コウイチ; SHIRAISHI, Kouichi; FUJIWARA, Motowo; AYUKAWA, Shigeru; IWASAKA, Yasunobu; et al. (National Institute of Polar Research, 1998)
P(論文) Lidar observations of polar stratospheric clouds (PSCs) were performed in the winter of 1996/97 at Ny-Alesund, Svalbard, Norway (79°N, 12°E). Corresponding to the appearance of an area colder than the estimated frost point of nitric acid trihydrate (NAT) above Ny-Alesund, PSCs were observed intermittently. As the temperature is lower than the NAT frost point, the peaks of scattering ratio (R) tend to increase and most PSC layers with large enhancement in R show negative correlation between R and depolarization ratio (δ). This suggests that the PSC layers were composed of liquid or small particles, which showed small values of δ even though the temperature was very low in that height range. During the period when the temperature profile showed large wave-like fluctuations, the detected PSCs varied remarkably in time and space. Heights of R peaks observed during that period did not conincide with the temperature minima which were measured once a day by rawinsonde. departmental bulletin paper